MEASURES TO PROMOTE INCLUSION IN THE COURT OF JUSTICE OF PERNAMBUCO (TJPE) (REMUNOM, 2025)
Discussing the importance of inclusive service in the public sector, especially for people with disabilities, is essential. The Court of Justice of Pernambuco (TJPE) is highlighted as an institution that faces challenges similar to other public spaces. To mitigate attitudinal barriers, the Judicial School of TJPE, aiming to implement inclusive practices, offers in its training program the distance learning course: Service for people with disabilities in public spaces. The research showed that the course significantly contributed to expanding inclusive awareness, strengthening ethical attitudes, and technically qualifying TJPE employees in serving people with disabilities. Despite the progress, structural challenges remain, such as attitudinal and architectural barriers and limited resources. Nevertheless, the data indicate a promising scenario for the consolidation of more inclusive practices in the public sector.